2014
DOI: 10.1095/biolreprod.114.119610
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA Methylation Analysis in Swine Reveals Conserved and Species-Specific Methylation Patterns and Highlights an Altered Methylation at the GNAS Locus in Infertile Boars1

Abstract: Male infertility is an increasing health issue in today's society for both human and livestock populations. In livestock, male infertility slows the improvement of animal selection programs and agricultural productivity. There is increasing evidence that epigenetic marks play an important role in the production of good-quality sperm. We therefore screened for specific or common epigenetic signatures of livestock infertility. To do so, we compared DNA methylation level in sperm DNA from fertile and infertile bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 76 publications
0
21
0
Order By: Relevance
“…Total RNAs were extracted from testis samples from three fertile control boars with normal semen parameters (Supplementary Table 1) and from the t(1;14) boar using the method described in Congras et al (2014). Three independent extractions from three samples were performed for each animal.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNAs were extracted from testis samples from three fertile control boars with normal semen parameters (Supplementary Table 1) and from the t(1;14) boar using the method described in Congras et al (2014). Three independent extractions from three samples were performed for each animal.…”
Section: Methodsmentioning
confidence: 99%
“…NESP55‐GNAS locus, which was found to be imprinted in cattle (Khatib et al, ), mice (Fröhlich et al, ), humans (Grybek et al, ), and pigs (Oczkowicz et al, ), covers more than 11 Kb on bovine chromosome 13. Congras et al () have previously described an altered methylation at this locus in infertile boars. A high sequence homology was found between pig and bovine sequences, so we opted to analyze the same region.…”
Section: Resultsmentioning
confidence: 93%
“…However, in contrast, genome-wide DNA methylation profiles of spermatozoa DNA, as well as methylation analysis on the GNAS promoter region of sperm treated with the pesticide, did not show evident alterations at the concentrations used for the experimental design. Nonetheless, our interest for GNAS was still justified by evidence reported in previous studies; higher methylation levels of GNAS promoter were found in sterile boars compared to fertile boars (Congras et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we identified 1080 alterations associated with low viability, 164 altered regions associated with low motility, and 12 alterations associated with low count (Table S2). Interestingly, in these analyses PEG10, MEST, and GNAS (commonly cited imprinted genes that are reportedly associated with male infertility in multiple mammalian species) were genes that had commonly altered methylation profiles (Poplinski et al, 2010;Congras et al, 2014). We assessed the distance from the transcription start site (TSS) of the regions identified to be associated with both low motility and low viability (Fig.…”
Section: Regional Methylation Alterationmentioning
confidence: 99%